2017
DOI: 10.4045/tidsskr.16.1103
|View full text |Cite
|
Sign up to set email alerts
|

Treningsindusert rabdomyolyse – en pasientserie

Abstract: He contributed to the design, data collection, analysis and interpretation, literature search, drafting and revision of the manuscript and has approved the submitted version. Kiarash Tazmini (born 1976), research fellow. The author has completed the ICMJE form and reports no conflicts of interest. CHRISTOFFER SCHREINER Department of Medicine Diakonhjemmet HospitalHe contributed to the design, data collection, obtaining consent, data interpretation, literature search, drafting and revision of the manuscript and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
7
0
5
Order By: Relevance
“…In our review of the English language medical literature, there were no reported cases of rhabdomyolysis associated with terbinafine, so the frequency of rhabdomyolysis associated with terbinafine is unknown. Another known cause of rhabdomyolysis is exercise [5]. We present a case of a patient who may have experienced exercise-induced rhabdomyolysis while using terbinafine to treat onychomycosis.…”
Section: Introductionmentioning
confidence: 99%
“…In our review of the English language medical literature, there were no reported cases of rhabdomyolysis associated with terbinafine, so the frequency of rhabdomyolysis associated with terbinafine is unknown. Another known cause of rhabdomyolysis is exercise [5]. We present a case of a patient who may have experienced exercise-induced rhabdomyolysis while using terbinafine to treat onychomycosis.…”
Section: Introductionmentioning
confidence: 99%
“…Det er ingen absolutt CK-grense for rabdomyolyse, men ofte brukes CK > 5-10 ganger referanseverdi eller CK > 5 000 E/l i blod, muskelsmerter og urinstiks positiv for blod som diagnostiske kriterier (1). Antallet pasienter innlagt med treningsindusert rabdomyolyse er økende i Norge (2)(3)(4). Smerte er en vesentlig del av det kliniske bildet (5), og de som innlegges er ofte relativt utrent for den aktuelle belastningen (6)(7)(8).…”
Section: Fortolkningunclassified
“…Forskjeller mellom muskelstølhet og aktivitetsutløst rabdomyolyse (2,3,5,20,21,24,(27)(28)(29)(30)(31)(32).…”
Section: Tabellunclassified
“…Nylig er det dokumentert økt forekomst av rabdomyolyse etter trening i Norge (18)(19)(20). Årsaken synes å vaere økt popularitet av svaert intensive former for trening.…”
Section: Rabdomyolyseunclassified